Constitutive expression of B7 restores immunogenicity of tumor cells expressing truncated major histocompatibility complex class II molecules. - Baskar, S (1993)
The inability of the autologous host to reject resident tumor cells is frequently the result of inadequate generation of tumor-specific T cells. Specific activation of T cells occurs after delivery of two signals by the antigen-presenting cell. The first signal is antigen-specific and is the engagement of the T-cell antigen receptor by a specific major histocompatibility complex antigen-peptide complex. For some T cells, the second or costimulatory signal is the interaction of the T-cell CD28 receptor with the B7 activation molecule of the antigen-presenting cell. In the present study, we demonstrate that mouse sarcoma cells genetically engineered to provide both T-cell activation signals stimulate potent tumor-specific CD4+ T cells that cause rejection of both engineered and wild-type neoplastic cells. Two other recent studies have also demonstrated that costimulation via B7 can improve tumor immunity. However, our study differs from these reports by two important observations. (i) One of these studies utilized mouse tumor cells expressing xenogenic viral antigens, and hence, the results are not applicable to wild-type resident tumors. Our study, however, demonstrates that coexpression of B7 by major histocompatibility complex class II+ tumor cells induces immunity in the autologous host that is specific for naturally occurring tumor antigens of poorly immunogenic tumors. (ii) In both earlier studies, only CD8+ T cells were activated after coexpression of B7, whereas in the present report, tumor-specific CD4+ T cells are generated. This report therefore illustrates the role of B7 activation molecule in stimulating potent tumor-specific CD4+ T cells that mediate rejection of wild-type tumors and provides a theoretical basis for immunotherapy of established tumors.